2019
DOI: 10.1534/g3.119.400752
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude ofCandida albicansStress-Induced Genome Instability Results from an Interaction Between Ploidy and Antifungal Drugs

Abstract: Organismal ploidy and environmental stress impact the rates and types of mutational events. The opportunistic fungal pathogen Candida albicans, serves as a clinically relevant model for studying the interaction between eukaryotic ploidy and drug-induced mutagenesis. In this study, we compared the rates and types of genome perturbations in diploid and tetraploid C. albicans following exposure to two different classes of antifungal drugs; azoles and echinocandins. We measured mutations at three different scales:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 66 publications
(102 reference statements)
0
37
0
Order By: Relevance
“…The extreme genome instability observed in tetraploids, is partly due to intrinsic highly labile nature. It has been well established that tetraploid C. albicans has higher levels of genome instability compared to diploids (18,(22)(23)(24), and this phenomenon is also observed in related yeast species (44)(45)(46)(47). However, the impact of genetic background on tetraploid genome stability has been extremely limited to date (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extreme genome instability observed in tetraploids, is partly due to intrinsic highly labile nature. It has been well established that tetraploid C. albicans has higher levels of genome instability compared to diploids (18,(22)(23)(24), and this phenomenon is also observed in related yeast species (44)(45)(46)(47). However, the impact of genetic background on tetraploid genome stability has been extremely limited to date (24).…”
Section: Discussionmentioning
confidence: 99%
“…As a highly heterozygous diploid (16), the C. albicans genome is highly labile and undergoes large-scale genome rearrangements like loss-of-heterozygosity (LOH) events and aneuploidy more frequently than small-scale DNA mutations. Furthermore, exposure to physiologically relevant stress conditions, including high temperature, oxidative stress, and antifungal drugs, increases LOH rates even further (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown in C. albicans that genome stability is altered by environmental triggers to promote the microevolution and adaptation of this species. For example, two recent studies found that C. albicans mutation rate is elevated during host infection [ 67 ], and in the presence of anti-fungal drugs [ 68 ] presumably to provide genetic raw material to the organism for survival under these stresses. Both studies also reveal the inconsistency of acquired genetic variation and how genome characteristics, such as differences in ploidy [ 68 ] and sub-telomeric chromatin structures [ 67 ], disproportionately elevate mutation mate.…”
Section: Chromatin Structure and The Availability Of Anti-fungal Rmentioning
confidence: 99%
“…For example, two recent studies found that C. albicans mutation rate is elevated during host infection [ 67 ], and in the presence of anti-fungal drugs [ 68 ] presumably to provide genetic raw material to the organism for survival under these stresses. Both studies also reveal the inconsistency of acquired genetic variation and how genome characteristics, such as differences in ploidy [ 68 ] and sub-telomeric chromatin structures [ 67 ], disproportionately elevate mutation mate. The mechanism by which such stress-induced mutagenesis arises remains to be determined, but taken together these findings suggest that regulators of genome architecture and chromatin structure may play a role in this process.…”
Section: Chromatin Structure and The Availability Of Anti-fungal Rmentioning
confidence: 99%